A new sponge-associated species, Syllis mayeri n. sp. (Polychaeta: Syllidae), with a discussion on the status of S. armillaris (Müller, 1776) - Musco, Luigi; Giangrande, Adriana (Scientia Marina, 2005)
In the framework of a study carried out along the Belizean coasts, a new species of syllid, Syllis mayeri n. sp., was found harboured by the sponge Ircinia strobilina. The description of this new taxon is given, and compared to other similar congeneric species and to some Mediterranean material from the southern Italian coast ascribed to S. armillaris. The new species is characterized by some stout compound chaetae with ypsiloid appearance, whose probable use for attaching to the host is hypothesized. Other diagnostic features are antennae, tentacular cirri and dorsal cirri of the anterior portion of the body that are longer than in similar, compared species. Moreover, the mid-body dorsal cirri are typically spindle-shaped. A discussion on the status of some sponge-associated taxa from tropical and subtropical seas attributed to the so-called cosmopolitan S. armillaris is also given.
Kristian Fauchald's Polychaeta DB